Toplumsal konumların dağılımında toplumsal kökenin süregiden etkisi - Yeşer TORUN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
This study addresses the relationship between education and meritocratic view grounded on the modern functionalist theory. In this theory it is argued that achieved characteristics are becoming more significant in the modern societies than ascribed characteristics for the access of social rewards. In this context, this study researches the role and effect of social origins –with regards to economic, social and cultural capital, ethnicity, religious identity and gender- on the selection and elimination process throughout school and work life. A qualitative approach is employed in the study. As a data collection instrument, a semi-structured interview form is used. The data is analyzed by using the qualitative content analysis method. The study indicates that ascribed characteristics such as economic, social and cultural capital ethnicity, religion, gender etc.- are very influential throughout school and work life and they still maintain its importance for his/her final social position